1986
DOI: 10.1111/j.1365-2273.1986.tb00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanisms of reduction of nasal mucociliary clearance in chronic sinusitis

Abstract: Nasal mucus was collected from 38 patients with chronic sinusitis. Following this collection, nasal mucociliary clearance (ST) was measured by the saccharin granule technique. Nasal mucus was used for in vitro frog palate clearance studies and then compared with the in vivo ST. The mucociliary transport rate of nasal mucus on mucus-depleted frog palate (MTR on frog palate) was 5.93 +/- 1.04 mm/min in the patients whose ST was within normal range (group A), and was 5.54 +/- 1.94 mm/min in the patients whose ST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Further, the goblet cell density in the polypoid group was lower compared to the edematous type, possibly because of the severe polypoid mucosal changes in chronic maxillary sinusitis. The abundance of submucosal glands in the postoperative antral mucosa showed continuing post-FESS recovery, which may have resulted in an abnormal mucous blanket [15].…”
Section: Discussionmentioning
confidence: 98%
“…Further, the goblet cell density in the polypoid group was lower compared to the edematous type, possibly because of the severe polypoid mucosal changes in chronic maxillary sinusitis. The abundance of submucosal glands in the postoperative antral mucosa showed continuing post-FESS recovery, which may have resulted in an abnormal mucous blanket [15].…”
Section: Discussionmentioning
confidence: 98%
“…Although multiple etiologies contribute to the development of CRS, a common pathophysiologic sequelae is ineffective sinonasal mucociliary clearance, resulting in stasis of sinonasal secretions with subsequent infection and/or persistent inflammation. Although the literature is contradictory regarding mucus viscosity [68][69][70], and basal ciliary beat frequency [69,[71][72][73][74], in CRS, recent work has suggested that a subset of patients with CRS have a blunted ciliary response to environmental stimuli [35 ].…”
Section: Mucociliary Clearance and Diseasementioning
confidence: 99%
“…[26][27][28][29][30][31][32] Possible reasons for impaired mucus transport in CRS are (1) alterations of viscoelastic properties of airway secretions, (2) reduced basal CBF, (3) impaired mechanical mucociliary coupling, and/or (4) blunted ciliary acceleration to particulate or noxious stimuli. 33 Interestingly, surgical intervention with functional endoscopic sinus surgery restores MCC to normal velocities between the 1st and 6th months postoperatively, [29][30][31][32]34,35 suggesting that the pathophysiological process(es) responsible for CRS-associated delayed MCC is reversible.…”
mentioning
confidence: 98%